2015
DOI: 10.1007/s11468-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Band High Refractive Index Susceptibility of Plasmonic Structures with Network-Type Metasurface

Abstract: We theoretically propose a simple plasmonic structure with network-type metasurface consisting of double-layer metal-dielectric network-type metasurface on the two-layer dielectric films. Multiple reflection bands with minimum full width at half maximum of 3 nm are achieved in the visible and near-infrared regions due to the excitation and hybridized coupling of localized surface plasmons, photonic mode, and optical cavity mode. The plasmonic structure with network-type metasurface also shows highly tunable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…The reflectivity dip is the minimum value when the refractive index of the dielectric layer is approximately 1.3. At the same time, the FWHM is around 1.85 nm, which is much narrower than that of the published narrowband absorber in the visible region [24, 28, 34, 39].
Fig.
…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…The reflectivity dip is the minimum value when the refractive index of the dielectric layer is approximately 1.3. At the same time, the FWHM is around 1.85 nm, which is much narrower than that of the published narrowband absorber in the visible region [24, 28, 34, 39].
Fig.
…”
Section: Resultsmentioning
confidence: 70%
“…Thus, the FOM can reach 233.5. As far as we know, the FOM is much higher than that of the previously published plasmonic refractive index sensor in visible region [24, 28, 34, 39]. The proposed plasmonic refractive index sensor shows good linearity, as shown in Fig.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…This sensor has a wavelength sensitivity exceeding 1000 nm/RIU and FOM of only 5 [25]. Liu et al demonstrated theoretically a plasmonic sensor based on the plasmonic structure with network-type metasurface on the two-layer dielectric films, which have the FOM of 68.57 [26]. Using Au bowtie nanoantenna arrays with metal-insulator-metal configuration, Lin simulated numerically a sensor with the FOM of 254 [27].…”
Section: Introductionmentioning
confidence: 99%